(untitled) (Bangladesh Journal of Botany, 2023)
Black rot disease caused by bacterium Xanthomonas campestris pv. campestris has been identified as major cause for low cabbage yields. The present study was conducted to evaluate the efficacy of various antibiotics and bioagents for controlling black rot disease and also their effect on extracellular polysaccharide secretion (EPS) of Xanthomonas campestris pv. campestris. Under in vitro conditions, bacterial proliferation and EPS production were examined on yeast peptone agar medium containing sucrose or trehalose with or without antibiotics. Number of Xanthomonas campestris pv. campestris on yeast peptone agar medium with Validamycin-A was less as compared to control. Extracellular polysaccharide secretion (EPS) was also inhibited on yeast peptone agar medium with antibiotic Validamycin-A. In vivo, disease intensity was recorded minimum in seed treatment + root dipping + foliar spray with Validamycin-A @ 500 µg/ml followed by seed treatment with Validamycin-A @ 500 µg/ml in comparison to control. Similarly, 45.61% higher cabbage yield was recorded in seed treatment + root dipping + foliar spray with Validamycin-A @ 500 as compared to untreated control. However, the antibiotic Validamycin-A which was found effective can be recommended to manage the disease. Bangladesh J. Bot. 52(4): 965-970, 2023 (December)